The role of the velocometer as an innovative tool for Paralympic coaches to understand wheelchair sporting training and interventions to help optimise performance - Goosey-Tolfrey, V. L.; Mason, B.; Burkett, B. (Sports Technology, 2012)
Speed, power, agility, coordination and flexibility are all foundations of athletic performance. Coaches and sport scientists often seek ways of obtaining accurate information on their performer's speed as this is a critical performance variable in many sports. In early days the use of ticker tape was used for the measurement of sprinting performance by providing intervals of time of a moving object. Nowadays more advanced techniques involving high-speed video cameras, speedometers and electronic timing gates are used. This article reviews the literature that is pertinent to the wheelchair athlete and describes the velocometer, a device that measures the intra-push profile of manual wheelchair propulsion. The purpose of this article is to review and challenge how this velocometer is currently being used to support the work of Paralympic coaches/sport scientists to help determine effective training strategies and to optimize performance. Specific sections analyze the importance of speed and the impact of Paralympic classification. The research findings revealed are predominantly related to the use of the velocometer within an applied sport science context. This information may be helpful in better understanding the concept of speed during wheelchair propulsion and the integration of the chair and athlete.